Coupled geophysics and geochemistry to record recent coastal changes of contaminated sites of the Bagnoli industrial area, Southern Italy. (5th November 2020) - Passaro, Salvatore; Gherardi, Serena; Romano, Elena; Ausili, Antonella; Sesta, Giulio; Pierfranceschi, Giancarlo; Tamburrino, Stella; Sprovieri, Mario
Abstract: The paper shows the results of a geochemical - geophysical survey on the decommissioned industrial area of Bagnoli (Naples, southern Italy). Analyses of 15 priority congeners of Polycyclic Aromatic Hydrocarbons (PAHs) were carried out on 21 sediment cores, collected on the beaches surrounding the old iron and steel industrial plant that was active over the last century. Anomalous high concentrations of PAHs were detected in this area, up to 87, 000 μg g −1 d.w. In particular, most congeners were embedded inside a mainly sandy layer, characterized by a dark colour and high resistivity values. The joined use of Electrical Resistivity Tomography, chemical data and direct observation of cores allowed a volumetric estimation of the polluted layer corresponding to 20, 200 m 3 . A total of 24, 100 m 3 of less polluted materials cover the dark, highly polluted layer. In addition, the geophysical-environmental approach helped to disentangle the deep interactions between the beach area, coastal changes and fluid vents. The actual coastal morphology is the result of historical, anthropic-driven rapid evolution that we reconstructed by using available historical images. The achieved results underline a crucial role played by combining geophysical and geochemical methodologies for a deeper and systematic understanding of anthropogenic impacts in coastal systems affected by multiple and combined stressors. Graphical abstract: Image 1 Highlights: Huge anthropic modification were introduced in the coastline at the Bagnoli brownfield site, Naples, Italy, during the past Century. The Bagnoli Coat is affected by high level of pollution, consisting in high concentrations (up to 87, 000 μg g -1  d.w) of PAH and an oil liquid phase.Geophysical and chemical constrains were combined to reconstruct the historical evolution of environmental impact in this area. Coastal changes have ruled the emplacement of polluted sediments. A potential time and space reconstruction is proposed.